Precautionary recapitalisation: time for a review? - Nicolas Véron (Bruegel, 2017)
The Bank Recovery and Resolution Directive (BRRD) of 2014, together with the initiation of banking union in the euro area, represent a regime change in EU banking sector policy. The BRRD replaces the prior assumption of public reimbursement of a failing bank's claimants (or bail-out) with one of mandatory burden sharing (or bail-in), thus reinforcing market discipline. The shift of preference from bail-out to bail-in represents major progress for the EU financial sector policy framework, and deserves continued support. Longstanding financial crisis experience suggests, however, that this shift cannot be absolute. The BRRD, accordingly, maintains the possibility of public support through government guarantees and through precautionary recapitalisation, which is the focus of this paper. Keeping open the option of precautionary recapitalisation is justified both by transitional considerations, as offering flexibility on the long and treacherous path towards a more complete banking union, and permanent considerations, as an available option for public intervention in dire crisis scenarios such as that experienced in the early autumn of 2008. The conditions set by the BRRD for precautionary recapitalisation are fairly restrictive. They include conditions on the viability and balance sheet testing of the bank in question, the competitive impact, the economic and financial stability environment and general principles that the intervention should be precautionary, temporary and proportionate. There have been only few actual cases of precautionary recapitalisation under the BRRD so far: two Greek banks in late 2015, whose precautionary recapitalisations using ordinary shares and contingent convertible bonds can currently be viewed as broadly successful, and very recently Monte dei Paschi di Siena in Italy. It was also requested by Banca Popolare di Vicenza and Veneto Banca, also in Italy, but not granted, suggesting the conditions for access to precautionary recapitalisation are meaningfully enforced by EU authorities. There is no immediate need for legislative reform of the parts of the BRRD that establish the possibility of precautionary recapitalisation, beyond making corrections to a few words in Article 32 that appear to result from hasty drafting. Implementation practice can be expected to draw lessons from early experience, including the need for an asset quality review as a prerequisite for precautionary recapitalisation in all cases except those where circumstances would make it practically infeasible. The broad review of the BRRD scheduled in 2018 should provide another opportunity to consider any need to amend the legislative basis for precautionary recapitalisation, possibly based on more lessons from practical experience in the meantime.
Keywords: 330